2006
DOI: 10.1189/jlb.0905509
|View full text |Cite
|
Sign up to set email alerts
|

Immune phenomena involved in the in vivo regression of fibrosarcoma cells expressing cell-associated IL-1α

Abstract: Constitutive expression of cell-associated, but not secreted, interleukin-1alpha (IL-1alpha) by oncogene-transformed fibrosarcoma cells induced regressing tumors in mice, a phenomenon that was abrogated by the IL-1 inhibitor, the IL-1 receptor antagonist (IL-1Ra). On the contrary, non-IL-1alpha-expressing tumor cells induce progressive tumors in mice. In vivo and ex vivo experiments have shown that regression of IL-1alpha-positive fibrosarcoma cells depends on CD8(+) T cells, which can also be activated in CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…Finally, in comparison to effector cells from WT mice, innate and specific antitumor effector cells from IL-1␣ Ϫ/Ϫ mice, i.e., NK cells, LAK cells, and CTL, displayed a reduced killing capacity, which correlated with reduced expression of perforin and granzyme B in purified NK cells from IL-1␣ Ϫ/Ϫ mice. The unique membrane-associated form of IL-1␣ is possibly of importance for its efficiency in activating antitumor immune responses, by acting as a focused adjuvant, through binding to IL-1RI, which are abundant on immunosurveillance cells, as has been demonstrated in our previous studies (24,25,(27)(28)(29)(30)(31). Membrane IL-1␣ may also be important in the effector phase of antitumor immunity, by enabling more avid binding between target tumor cells and immunosurveillance effector cells that leads to better killing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, in comparison to effector cells from WT mice, innate and specific antitumor effector cells from IL-1␣ Ϫ/Ϫ mice, i.e., NK cells, LAK cells, and CTL, displayed a reduced killing capacity, which correlated with reduced expression of perforin and granzyme B in purified NK cells from IL-1␣ Ϫ/Ϫ mice. The unique membrane-associated form of IL-1␣ is possibly of importance for its efficiency in activating antitumor immune responses, by acting as a focused adjuvant, through binding to IL-1RI, which are abundant on immunosurveillance cells, as has been demonstrated in our previous studies (24,25,(27)(28)(29)(30)(31). Membrane IL-1␣ may also be important in the effector phase of antitumor immunity, by enabling more avid binding between target tumor cells and immunosurveillance effector cells that leads to better killing.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with IL-1␤, IL-1␣ is secreted in only a limited manner, especially by macrophages, and thus induces limited inflammatory responses and in its membrane-associated form it is immunostimulatory. Indeed, malignant fibrosarcoma cells which express cell-associated IL-1␣, which acts as a focused adjuvant, exhibit increased immunogenicity and induce regressing tumors in mice, through activation of anti-tumor cell immunity (24,25,(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Using transfectants of fibrosarcoma cells with active forms of the IL-1 molecules, we have shown that IL-1β secreted by malignant cells contributes to increased tumor invasiveness and angiogenesis, as well as to general anergy in the host, mediated by myeloid precursor cells. In contrast, fibrosarcoma cell lines overexpressing IL-1α, mainly on the cell surface or intracellularly, are highly immunogenic and induce regressing tumors, due to eradication of the malignant cells by the host's immune system (Song et al, 2003(Song et al, , 2005Dvorkin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, IL-1α is active as an intracellular precursor (proIL-1α), a membrane form, and as a secreted form (mature form, 18 kDa) [10]. Membrane IL-1α (ß23kDa) is thought to be immunostimulatory [11], while cytosolic proIL-1α controls homeostatic functions, such as gene expression and control of proliferation and differentiation [12]. IL-1α is not secreted and retained in cells during apoptosis process [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the membrane IL-1α even slightly protected the mice from CCl 4 -induced acute liver injury. It has been suggested that membrane IL-1α could function as an adhesion molecular to promote immune responses [11,50]. The mechanism of its protective role in acute liver injury still needs further investigation.…”
mentioning
confidence: 99%